Implementation of Women's Elderly Exercises in RW 08 Jayagiri Lembang Village, West Bandung District - Fuadah, Fahmi; Saragih, Berlyna D.; Sinaga, Herwinda; Purnasari, Henni; Harun, Iriyanti; Adi, Yohanes (CV Media Inti Teknologi, 2024)
Hypertension is a health problem that is often encountered in the elderly and can increase the risk of heart disease and stroke. Elderly exercise has been recognized as having benefits in improving physical and psychological health. This community service aims to carry out the tridharma activities of higher education which are always held once a year. This study aims to evaluate the effect of an elderly exercise program on the management of hypertension in the elderly. The method used was checking the blood pressure of the elderly before and after the implementation of the elderly exercise program which was carried out on September 13 2023. This community service was carried out in RW 08 Jayagiri Village, Lembang District, West Bandung Regency. Followed by 32 elderly women. The results of the study showed significant changes in blood pressure from previously having high blood pressure above 140/90 as much as 70%. After carrying out the elderly exercise, blood pressure was checked again with the results decreasing below 140/90 by 65%. The conclusion from this community service activity is that there is a significant reduction in blood pressure in the elderly after carrying out elderly exercise. Elderly exercise can be an effective approach in treating hypertension in the elderly. The community service activities carried out went well. This can be seen from the enthusiasm of the elderly women during the activity.